2016
DOI: 10.1097/dss.0000000000000597
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Nonablative Fractional Erbium Laser 1,340 nm and Microneedling for the Treatment of Atrophic Acne Scars

Abstract: This study shows that both nonablative fractional laser 1,340 nm and microneedling are comparable and effective in the treatment of atrophic acne scars. Microneedling is well tolerated, with fewer side effects and lower down time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(36 citation statements)
references
References 21 publications
1
34
0
1
Order By: Relevance
“…Subcision, needling and PRP are minimally invasive modalities and have the advantages of short downtime and low cost . The combination treatment used in the present study is effective in severe (grade 4) acne scarring and well tolerated in Fitzpatrick skin types III to V. To our knowledge, this is the first study that has combined these minimally invasive modalities.…”
Section: Discussionmentioning
confidence: 99%
“…Subcision, needling and PRP are minimally invasive modalities and have the advantages of short downtime and low cost . The combination treatment used in the present study is effective in severe (grade 4) acne scarring and well tolerated in Fitzpatrick skin types III to V. To our knowledge, this is the first study that has combined these minimally invasive modalities.…”
Section: Discussionmentioning
confidence: 99%
“…17 Cachafeiro et al compared MN and non-ablative fractional erbium laser1, 340 nm treated atrophic skin scars with no statistically significant difference. 18 Dogra et al reported utility of MN for treating atrophic acne scars in Asian population. 19 Sharad 2011 studied MN and 35% glycolic acid peels for treatment of atrophic box type, rolling type with PIH in dark skin showed significant improvement.…”
Section: Scarsmentioning
confidence: 99%
“…101 Numerous studies support the utility of microneedling without the augmentation of an energy-based device in the treatment of acne and other scar types. [102][103][104][105] In 3 studies involving 91 patients (skin types III-V) investigating RFM in atrophic acne, various acne scar scoring systems consistently reported a moderate improvement in scar appearance after treatment. 100,106,107 RFM offers superior results for ice-pick and boxcar acne scars than rolling scars 108 and appears to offer a more dramatic improvement in acne scarring than bipolar RF alone.…”
Section: Fractional Radiofrequencymentioning
confidence: 99%